Who Bears Flood Risk? Evidence from Mortgage Markets in Florida - Sastry, Parinitha (Review of Financial Studies, 2026)
Government-provided flood insurance contracts have strict coverage limits, leaving some households underinsured against flood risk. This paper exploits these strict coverage limits as well as staggered flood map updates to show that mortgage lenders screen for uninsurable flood risk by requiring lower loan-to-value ratios at origination. This credit rationing leads delinquency rates to equalize inside and outside of flood zones, and shifts the composition of mortgage borrowers in flood zones toward richer and higher credit quality individuals. I conclude that lenders reduce credit supply when they retain residual uninsured exposures to flood risk, which has distributional consequences for flood zones.